Moral Expansiveness Around the World: The Role of Societal Factors Across 36 Countries. Issue 3 (April 2023) - Kirkland, Kelly; Crimston, Charlie R.; Jetten, Jolanda; Rudnev, Maksim; Acevedo-Triana, Cesar; Amiot, Catherine E.; Ausmees, Liisi; Baguma, Peter; Barry, Oumar; Becker, Maja; Bilewicz, Michal; Boonyasiriwat, Watcharaporn; et al.
What are the things that we think matter morally, and how do societal factors influence this? To date, research has explored several individual-level and historical factors that influence the size of our 'moral circles.' There has, however, been less attention focused on which societal factors play a role. We present the first multi-national exploration of moral expansiveness—that is, the size of people's moral circles across countries. We found low generalized trust, greater perceptions of a breakdown in the social fabric of society, and greater perceived economic inequality were associated with smaller moral circles. Generalized trust also helped explain the effects of perceived inequality on lower levels of moral inclusiveness. Other inequality indicators (i.e., Gini coefficients) were, however, unrelated to moral expansiveness. These findings suggest that societal factors, especially those associated with generalized trust, may influence the size of our moral circles.